The discretionary authority of the judge to temporarily suspend the implementation of the contract - a comparative study - Samir Hamid, Assistant Professor Dr. Safana; Haneen Mahmood Abrahim , (The college of law and political science journal, 2023)
Each party to the contract shall perform the contract in accordance with what it contains in the manner that requires goodwill whenever it is validly concluded in accordance with the law. However, it may preclude performing the contract, such that it is impossible for the party to the contract to perform his obligation for a reason beyond his control, which leads to terminate the contract by force of law. However, this principle is not applied in all conditions. The nature of the impossibility may allow the judge to avoid to termination as a means to dissolve the contract. Other means shall also be used that would retain the contract. After the contract is being concluded and during the contract is being performed, a temporary impossibility occurs, which is expected to disappear in the near future. This impossibility may preclude the obligor to perform his obligation, and the other party had nothing to do with this impossibility as well as could not have expected it to happen. The judge may then dismiss the termination claim and rule to suspend performing the contract, the contract shall be resumed after the impossibility disappears. This is to preserve the contract as a legal entity, as well as to seek the possibility to perform the contract after the obstacle disappears that led to the suspension. The ruling to suspend performing the contract due to temporary impossibility gives rise to obligations that the parties to the contract are obliged to perform, such as the obligation to seek to remove the reason of impossibility, the obligation not to disclose secrets, and the obligation to take measures required to preserve the subject of the contract.